Narrative of a Practice for the Adaptation and Use of a Training tool for Evaluative Judgment Based on Concordance - Deschênes, Marie-France; Dionne, Eric; Dorion, Michelle (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2023)
Opportunities are rare for future teachers to test their interpretation of complex, uncertain, or ambiguous questions in learning assessment and to obtain subsequent formative feedback. This article proposes a pedagogical practice based on the adaptation and use of a Concordance of Judgment educational tool to exercise future teachers’ evaluative judgment. The theoretical foundations of the educational tool, the principles of its design, as well as the contextual factors that have influenced its adaptation in an educational context are discussed. This analysis identifies benefits of using the tool to promote the development of teachers’ evaluative judgment.